Effect of different constant and alternative temperatures and light situations on germination behavior of two Purslane (Protulaca oleracea L.) populations - Golzardi, F; Vaziritabar, Y; Asilan, K Sadat; Ashraf, M; Ebadi, SZ; Sarvaramini, SH (International Journal of Natural Sciences, 2016)
This study was carried out to investigate the germination behavior of two purslane populations (Karaj and Ahvaz), the effect of constant temperatures under two light regimes (12 hrs light/dark and continuous dark), alternative temperatures (day/night) and the lighting/darkness periods on purslane germination. The study was conducted in a randomized complete blocks design with four replications. The results showed that the highest percentage and germination rate in constant temperatures under two light regimes in Karaj mass (continuous darkness) and Ahvaz (12/12 hrs light/darkness), respectively at 25 and 30 °C (Optimum temperature) was observed. Purslane percentage and germination rate changes in alternating temperature (day/night) showed, the maximum values of both masses achieved at 30/20°C alternative temperature. According to result, by getting away from the optimum temperature, the germination percentage and its rate tends to have a descending process in both thermal experiments (alternative and constant temperature tests). Also the effect of different darkness/light periods on purslane percentage and germination rate showed, at (0/24) constant darkness treatment these traits got to the lowest point. The highest percentage and germination rates in Karaj and Ahvaz populations, respectively observed at 0/24, 12/12, 10/14 and 8/16 treatments; which had no statistical difference. Radicle length, shoot length and fresh weight of seedlings in both populations at constant temperatures under both light regimes at 20 to 30 °C and alternative temperatures (light/dark) at 30/20 °C had the highest values. International Journal of Natural Sciences (2014), 4(2) 13-21